2012
DOI: 10.1093/annonc/mds096
|View full text |Cite
|
Sign up to set email alerts
|

Extranodal natural killer/T-cell lymphoma from skin or soft tissue: suggestion of treatment from multinational retrospective analysis

Abstract: In conclusion, we identified the prognostic value of KPI, and we suggest a treatment recommendation according to the TNM (tumour-node-metastasis) stage. Radiotherapy with/without chemotherapy seemed to be optimal in localized disease. In advanced stages, a more aggressive treatment regimen with newer agents should be sought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 21 publications
9
39
0
Order By: Relevance
“…Similar significant differences in OS and PFS between RT and CT alone were also observed in the adjusted population. These results are consistent with other studies that compared survival across different treatments in earlystage NKTCL, 1,3,7,[18][19][20][21]30,33 with reported 5-year OS rates ranging from 50% to 90% after RT vs ,30% for CT alone. The striking difference in 5-year OS (.20%) between RT and CT alone suggests RT is an essential treatment of early-stage NKTCL and that CT alone should not be routinely administrated.…”
Section: Blood 17 September 2015 X Volume 126 Number 12 Risk-adaptesupporting
confidence: 91%
See 1 more Smart Citation
“…Similar significant differences in OS and PFS between RT and CT alone were also observed in the adjusted population. These results are consistent with other studies that compared survival across different treatments in earlystage NKTCL, 1,3,7,[18][19][20][21]30,33 with reported 5-year OS rates ranging from 50% to 90% after RT vs ,30% for CT alone. The striking difference in 5-year OS (.20%) between RT and CT alone suggests RT is an essential treatment of early-stage NKTCL and that CT alone should not be routinely administrated.…”
Section: Blood 17 September 2015 X Volume 126 Number 12 Risk-adaptesupporting
confidence: 91%
“…The outcomes for CT alone in early-stage NKTCL have been poor (CR, 20%-50%; overall response rate, 50%-70%; 5-year OS, 10%-35%, and even poorer PFS). [1][2][3]18,19,[30][31][32][33] Similarly, we confirmed the unfavorable prognosis of early-stage patients treated with CT alone-regardless of regimens-and obtained a significant survival improvement after RT (in both multivariable and PSM analysis). In the unadjusted population, 5-year OS was only 33.9% for CT alone compared with 69.6% for RT alone and 67.7% for RT with or without CT.…”
Section: Blood 17 September 2015 X Volume 126 Number 12 Risk-adaptesupporting
confidence: 73%
“…Radiotherapy with or without chemotherapy also resulted in better OS than chemotherapy. 65 In another retrospective study where PET/CT was used to exclude occult nasal primaries, 11 patients with nonnasal lymphomas treated with SMILE had an ORR of 72.7%, with CR achieved in 54.5%. 24 Current data indicate that localized nonnasal lymphomas might not fare as well as nasal lymphomas.…”
Section: Treatment Of Localized Disease Outside the Nasal Regionmentioning
confidence: 99%
“…Recent studies showed that for localized disease, concurrent chemoradiation and chemotherapy yielded a long-term survival of 70-80 % [8,9]. However, in cases with advanced stage disease or in extranasal cases, long-term survival beyond 1 year is extremely rare [1,4,[10][11][12]. Even high-dose chemotherapy and auto-hematopoietic stem cell transplantation cannot overcome the refractoriness [13].…”
Section: Introductionmentioning
confidence: 99%